Digitization Capacity and Skills of Academic Librarian in Nigeria - Adeleke, Akinniyi A (Redeemer’s University, Nigeria, 2016)
Increasing number of Nigerian universities is devising creative means of increasing their digital contents in the public domain by digitizing intellectual outputs of their faculty members. Digitization accords academic institutions the opportunity of making their institutional resources available thereby increasing their visibility and better performance in ongoing web ranking of world universities. However, certain skill sets and competencies are required by librarians who are responsible to establish and maintain digital collections in their respective institutions. This study therefore to investigated the level of librarians ’possession of these skills. A survey was conducted on librarians in eleven selected private and public universities in Nigeria that have minimum ICT infrastructure required for digitization. Eighty six librarians responded and data analysis revealed that digitization was still at its infancy in the libraries and few librarians were involved in the process. The study also found librarians score themselves below average in many of the specific digitization skills even though they considered them important. Also, majority of the librarians had no formal professional training in digitization and only a few spent time for personal skills development in the process.
Keywords: Digitization; institutional resources